Dextran 40 hybrid biomimetic bismuth-nanoflower designed for NIR II-triggered hypoxic tumor thermoradiotherapy via macrophage escape. (15th June 2023) - Wen, Jing; Liu, Chang; Liu, Ji; Wang, Lu; Miao, Si; Chen, Daquan; Wang, Qiyue; Huo, Meirong; Shen, Yan
Abstract: At present, NIR-II-triggered photothermal biomedical applications are limited by complex synthesis reactions, mediocre photothermal conversion efficiency, and difficult degradation. Herein, we prepared biodegradable Bi flower-like nanoparticles (phospholipid-modified Bi nanoflowers, BNFs) with high photothermal conversion efficiency (∼33.52 %) in NIR-II by a simple method and then modified them with the red blood cell membrane and dextran 40 (DRBCM) to improve their in vitro stability, to escape macrophages clearance and to enhance tumor accumulation. Dextran coating onto the surface of particles as a dispersant shell stabilizes inorganic particles by maintaining the surface charges and creating steric repulsions upon compression of neighboring polymer chains. In vitro and in vivo experiments proved that combined thermoradiotherapy of DRBCM-BNFs exhibited significantly enhanced tumor inhibition efficacy than monotherapy with good biocompatibility and low toxicity due to its biodegradability. Furthermore, the mechanism studies demonstrated that DRBCM-BNFs could serve as a nano sensitizer to promote the thermoradiotherapy under NIR-II illumination and X-ray irradiation, by downregulating heat shock protein 70 (HSP70) and phosphorylated-p65 (p-p65) to reduce the thermal resistance and radioresistance of tumor cells and increasing the expression of apoptosis-related protein cleaved caspase-3. In conclusion, DRBCM-BNFs could be a promising green delivery platform for the sensitization of synergistic thermoradiotherapy. Graphical abstract: Unlabelled Image